Skin Perfusion Pressure Is a Prognostic Factor in Hemodialysis Patients. (2nd April 2012) - Hatakeyama, Shingo; Saito, Masaaki; Ishigaki, Kumiko; Yamamoto, Hayato; Okamoto, Akiko; Ishibashi, Yusuke; Murasawa, Hiromi; Imanishi, Kengo; Tokui, Noriko; Okamoto, Teppei; Suzuki, Yuichiro; Sugiyama, Naoki; et al.
Abstract : Peripheral arterial disease (PAD) is common in hemodialysis patients and predicts a poor prognosis. We conducted a prospective cohort study to identify risk factors for PAD including skin perfusion pressure (SPP) in hemodialysis patients. The cohort included 373 hemodialysis patients among 548 patients who received hemodialysis at Oyokyo Kidney Research Institute, Hirosaki, Japan from August 2008 to December 2010. The endpoints were lower limb survival (peripheral angioplasty or amputation events) and overall survival of 2 years. Our results showed that <70 mmHg SPP was a poor prognosis for the lower limb survival and overall survival. We also identified age, history of cardiovascular disease, presence of diabetes mellitus, smoking history, and SPP < 70 mmHg as independent risk factors for lower limb survival and overall survival. Then, we constructed risk criteria using the significantly independent risk factors. We can clearly stratify lower limb survival and overall survival of the hemodialysis patients into 3 groups. Although the observation period is short, we conclude that SPP value has the potential to be a risk factor that predicts both lower limb survival and the prognosis of hemodialysis patients.